Contentious episodes in the age of austerity studying the dynamics of government-challenger interactions - Bojár, Ábel 1983-; Kriesi, Hanspeter 1949-; Hutter, Swen 1978-; Gessler, Theresa 1989- (Cambridge University Press, 2021)
Based on extensive data and analysis of sixty contentious episodes in twelve European countries, this book proposes a novel approach that takes a middle ground between narrative approaches and conventional protest event analysis. Looking particularly at responses to austerity policies in the aftermath of the Great Recession (2008-2015), the authors develop a rigorous conceptual framework that focuses on the interactions between three types of participants in contentious politics: governments, challengers, and third parties. This approach allows political scientists to map not only the variety of actors and actor coalitions that drove the interactions in the different episodes, but also the interplay of repression/concessions/support and of mobilization/cooperation/mediation on the part of the actors involved in the contention. The methodology used will enable researchers to answer old (and new) research questions related to political conflict in a way that is simultaneously attentive to conceptual depth and statistical rigor
Title from publisher's bibliographic system (viewed on 05 Nov 2021)
Introduction: A new approach for studying political contentious episode analysis / Hanspeter Kriesi, Swen Hutter, Abel Bojar, Argyrios Altiparmakis, Theresa Gessler, Sophia Hunger, Katia Pilati, Julia Schulte-Cloos -- Selecting and coding contentious episodes / Hanspeter Kriesi, Swen Hutter, Abel Bojar, Argyrios Altiparmakis, Theresa Gessler, Sophia Hunger, Katia Pilati, Julia Schulte-Cloos -- The economic and political context of the episodes / Hanspeter Kriesi and Sophia Hunger -- Conceptualizing, measuring and mapping contentiousness / Swen Hutter and Theresa Gessler -- Actors configurations and coalitions in contentious episodes / Swen Hutter and Theresa Gessler -- Action sequences and their dynamic indicators of contention / Abel Bojar and Argyrios Altiparmakis -- Outcomes--government responsiveness / Julia Schulte-Cloos and Sophia Hunger -- Interaction dynamics in contentious episodes : path-dependence, tit-for tat and constructive mediation / Abel Bojar and Hanspeter Kriesi -- The governments' reactions to challengers and third-parties / Hanspeter Kriesi -- The effect of repression on protest / Katia Pilati -- Turning points / Abel Bojar -- The Greek case / Argyrios Altiparmakis -- Conclusion / Abel Bojar, Hanspeter Kriesi, Swen Hutter
Keywords: Conflict management / European Union countries / Case studies; Recessions / European Union countries; Global Financial Crisis, 2008-2009; Government, Resistance to / European Union countries / Case studies; European Union countries / Politics and government / Case studies; European Union countries / Economic policy; European Union countries / Foreign economic relations / Case studies